2014
DOI: 10.1016/j.sjopt.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile and complications of autologous limbal conjunctival transplantation for primary pterygium

Abstract: Pterygium occurred predominantly in the younger population group 36.9 mm (±12.82) probably due to the increased outdoor activity with high exposure to sunlight and dusty atmosphere. Absence of recurrences was probably attributable to the smaller pterygium size of 1.67 mm (±4.23), use of the autologous limbal conjunctival graft and treatable intra and post operative complications successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…There was no recurrence in our study. It is comparable to those by Prabhakar et al [13], Bastola, [8] and Das et al [14] There was no recurrence in those study too, but the difference was that we used vicryl 8-0 suture while Prabhakar et a1. Beside longer surgical time, graft suturing also carries the risk of complications like granuloma formation, and discomfort with exposed suture ends after surgery, and if non-absorbable stitches are used there is the need for suture removal.…”
Section: Discussionsupporting
confidence: 87%
“…There was no recurrence in our study. It is comparable to those by Prabhakar et al [13], Bastola, [8] and Das et al [14] There was no recurrence in those study too, but the difference was that we used vicryl 8-0 suture while Prabhakar et a1. Beside longer surgical time, graft suturing also carries the risk of complications like granuloma formation, and discomfort with exposed suture ends after surgery, and if non-absorbable stitches are used there is the need for suture removal.…”
Section: Discussionsupporting
confidence: 87%
“…18,25 Similar observations were made both by Rohatgi S and Prabhakar SK who in their respective studies found that approximately 92% cases of pterygium belonged to nasal side. 5,20 In present study, progressive pterygium was present in 80% of patients whereas atrophic in 20% of patients. Similar observation was made by Chavan WM et al in their study where they found progressive pterygium in 72.4% eyes and atrophic in 27.6% eyes.…”
Section: Discussionsupporting
confidence: 51%
“…Prabhakar SK also concluded that males suffered more than females. 20 In this study, it was found that higher incidence of pterygium was in rural folk 66.67% who are exposed more to heat, dust, sun glare and atmospheric irritants. The tendency of prevalence of pterygium in rural area is more because of constant exposure of persons to more open and dusty environment in comparison to urban people.…”
Section: Discussionmentioning
confidence: 74%
“…Pterygium is horizontal, most frequently nasal, and grows across the limbus invading Bowman´s layer; whereas pseudopterygium can be located anywhere, most frequently in an oblique orientation, and is not adherent to the limbus [ 4 ]. Thus, to differentiate between a pseudopterygium and a pterygium, it is important to verify whether the conjunctival neoformation is really attached to the cornea [ 9 ]. Prabhakar et al [ 9 ].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…It is known that pseudopterygium can be caused by corneal degenerations, such as marginal Terrien’s degeneration, or by corneal injuries, such as chemical or thermal burns [ 4 ]. However, there are other possible causes described in the literature, namely iatrogenic limbal damage, limbus auto-transplant, or chronic inflammation, among others ( Figure 2 ) [ 4 , 6 , 8 , 9 ]. It is important to distinguish pseudopterygium from true pterygium.…”
Section: Introductionmentioning
confidence: 99%